Workplace abuse and economic exploitation of children working in the streets of Latin American cities (2010)
This study presents the prevalence of, and factors associated with workplace abuse and economic exploitation among 584 children ages 5 to 17 working in the streets of the Latin American cities of Bogotá, Lima, Quito, and São Paulo. Each additional 10 hours/week of children's work in the streets increased workplace abuse prevalence by 8% (odds ratio [OR], 1.08; 95% confidence interval [95%CI], 1.01-1.19). Suffering an occupational injury was associated with abuse (OR, 1.70; 95%CI, 1.13-2.57). Participation in begging was associated with an almost five-fold increase in economic exploitation (OR, 4.94; 95%CI, 1.96-12.48). Children residing with their mothers were 2.6 times more likely to experience economic exploitation (OR, 2.61; 95%CI, 1.58-4.33), reflecting our definition of economic exploitation in which a child's income is confiscated by parents, even if used for basic family needs. Increased health care coverage and conditional cash transfer programs are recommended to improve the situation.